Biocrusts under photobiotic and climate change stress: linking criticality and the functional response of N cycling in endoliths and biological soil crusts of Chilean arid environments - Abades - Torres; Sebastián (2023)
PROJECT RESULTS: Describe the results of your research in reference to its original and/or modified Project objectives. The maximum extension of this section is 5 pages (Arial or Verdana font, size 10). 1.- Assess the relationship of N fixation activity as a function of diversity and species composition within biocrusts, using an elevational transect along which UV, temperature and precipitation changes. The main indices to quantify and compare diversity will be species richness, community similarity, beta diversity (as a measure of variability across samples) and relative abundance of operative taxonomic units derived from metagenomic analyses. Project results related to this objective contributed totally or partly to 6 articles. Multiple relationships between environmental conditions and a broad set of functional and species diversity metrics were explored and analyzed. Specifically, we took advantage of the natural experimental conditions offered by the elevational transect that exists in the desert area of northern Chile to document systematic changes of microbial community structure in response to multiple stressors. For instance, several patterns of biocrust and/or soil microbial communities were reported in the article “Soil bacterial community structure of fog-dependent Tillandsia landbeckii dunes in the Atacama Desert” published in PLANT SYSTEMATICS AND EVOLUTION. Similarly, this objective contributed to the development of a multifunctionality index and its assessment at global scales in the high impact article “Multiple elements of soil biodiversity drive ecosystem functions across biomes” published in NATURE ECOLOGY & EVOLUTION. Another contribution that benefited from our research questions and protocols lead to the high impact article: “The influence of soil age on ecosystem structure and function across biomes” published in NATURE COMMUNICATIONS, allowing us to scale up our research and scope from regional to global scales. Fondecyt Iniciación FONDECYT Regular 2017 Proyectos de ...